2009
DOI: 10.1101/gad.1804409
|View full text |Cite
|
Sign up to set email alerts
|

A Rab escort protein integrates the secretion system with TOR signaling and ribosome biogenesis

Abstract: The coupling of environmental conditions to cell growth and division is integral to cell fitness. In Saccharomyces cerevisiae, the transcription factor Sfp1 couples nutrient status to cell growth rate by controlling the expression of ribosome biogenesis (Ribi) and ribosomal protein (RP) genes. Sfp1 is localized to the nucleus in rich nutrients, but upon nutrient limitation or target of rapamycin (TOR) pathway inhibition by rapamycin, Sfp1 rapidly exits the nucleus, leading to repression of the Ribi/RP regulons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 62 publications
(145 reference statements)
3
70
0
Order By: Relevance
“…In budding yeast, a group of over 200 co-regulated genes, termed the ri bosome bi ogenesis (RiBi) cluster, must coordinate the assembly of 4 rRNA molecules transcribed by RNA pol I and RNA pol III with 79 ribosomal proteins (RPs) whose mRNAs are transcribed by RNA pol II from 138 ORFs scattered throughout the genome. This complex process of ribosome production is coupled to nutrient availability and is down-regulated at multiple levels both during starvation and under conditions of cellular stress [14]. …”
Section: Introductionmentioning
confidence: 99%
“…In budding yeast, a group of over 200 co-regulated genes, termed the ri bosome bi ogenesis (RiBi) cluster, must coordinate the assembly of 4 rRNA molecules transcribed by RNA pol I and RNA pol III with 79 ribosomal proteins (RPs) whose mRNAs are transcribed by RNA pol II from 138 ORFs scattered throughout the genome. This complex process of ribosome production is coupled to nutrient availability and is down-regulated at multiple levels both during starvation and under conditions of cellular stress [14]. …”
Section: Introductionmentioning
confidence: 99%
“…So far, the GFP library has seen limited use for exploring cell polarity pathways-one screen identified proteins that localize to the mating projection in pheromone-treated cells [89]. A more common approach has been to study changes in the localization of cell polarityspecific proteins fused to a fluorescent moiety in the deletion collection or in the context of gene overexpression [53,[90][91][92][93][94][95][96][97][98]. For instance, the deletion mutant array was screened for mislocalization of modified Snc1-GFP, yeast synaptobrevin, to identify novel regulators of its internalization [53].…”
Section: (A) Genetic Assaysmentioning
confidence: 99%
“…To date, image-based screens using the yeast deletion and other arrayed collections have collected static images in a single focal plane [53,[90][91][92][93][94][95][96][97][98]. However, cell polarity is highly dynamic, and future analyses will involve the high-throughput acquisition of three-and fourdimensional spatial and temporal image sequences, using multiple fluorescent markers to highlight numerous compartments simultaneously.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…by Rabs seem to be coupled to pre-mRNA splicing 324 and nutrient sensing (Fujimura et al 1994, Jacoby 325 et al 1998, Bialek-Wyrzykowska et al 2000 and Tyers 2009) in yeast Saccharomyces cerevisiae as is 327 described in later sections. On the other hand, the 328 whole process of Rab geranylgeranylation in yeast is 329 strictly dependent on the GGPP substrate availability 330 (Miaczynska et al 2001) and the genes responsible 331 for GGPP synthesis are often found in genetic 332 screens together with the RGGT complex (Newman 333 and Ferro-Novick 1987, Vincent et al 2003, Singh 334 and Tyers 2009 (Witter and Poulter 1996).…”
mentioning
confidence: 99%
“…mrs6 overex-859 pression caused a decrease in cell size on non-860 fermentable carbon sources (Ragnini et al 1994) but 861 depletion caused an increase in cell size in poor nutri-862 ents (Singh and Tyers 2009). An opposite effect should 863 have been expected from a simple secretory system 864 perturbation.…”
mentioning
confidence: 99%